Modifying LFSR of ZUC to Reduce Time for Key-Stream Generation - Muthalagu, Raja; Jain, Subeen (Journal of Cyber Security and Mobility, 2017)
ZUC is stream-cipher which generates 32-bit key-stream by using 128-bit initial key and 123-bit initial vector. It encrypts the plaintext data to produce cipher-text data. The 128-EEA3 encryption and 128-EIA3 authentication algorithms are based on ZUC which are specified for use in 3GPP cellular communications systems. The algorithm is divided in three stages: LFSR (Linear Feedback Shift Register), Bit Reorganization (BR) and, Non-Linear Function. In this paper, we are going to discuss about our modifications proposed for LFSR along with small change in operation of Non-linear Function which can reduce time for generating key-stream. Many attacks based on weakness of LFSR due to its linearity are proposed which in turn makes ZUC susceptible to various attacks based on LFSR. As we know in the structure of LFSR, non-linearity is provided in last block of LFSR by feedback operation while all other being clocked with previous value of LFSR, so we have introduced bit-shifting and circular shift operations on few blocks of LFSR output of which will be taken as input to other blocks of LFSR.